2018
DOI: 10.1101/278903
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proteome-level assessment of origin, prevalence and function of Leucine-Aspartic Acid (LD) motifs

Abstract: ABSTRACT:Short Linear Motifs (SLiMs) contribute to almost every cellular function by connecting appropriate protein partners. Accurate prediction of SLiMs is difficult due to their shortness and sequence degeneracy. Leucine-aspartic acid (LD) motifs are SLiMs that link paxillin family proteins to factors controlling (cancer) cell adhesion, motility and survival. The existence and importance of LD motifs beyond the paxillin family is poorly understood. To enable a proteome-wide assessment of these motifs, we de… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 83 publications
0
11
0
Order By: Relevance
“…Focal Adhesion Kinase (FAK) is a multi-domain non-receptor protein tyrosine kinase (PTK) found in metazoans and also in the unicellular eukaryote Capsaspora owczarzaki [ 1 , 2 ]. FAK is a multifunctional protein that integrates and transduces signals perceived through integrin or growth-factor receptors into cytoplasmic and nuclear responses.…”
Section: Introductionmentioning
confidence: 99%
“…Focal Adhesion Kinase (FAK) is a multi-domain non-receptor protein tyrosine kinase (PTK) found in metazoans and also in the unicellular eukaryote Capsaspora owczarzaki [ 1 , 2 ]. FAK is a multifunctional protein that integrates and transduces signals perceived through integrin or growth-factor receptors into cytoplasmic and nuclear responses.…”
Section: Introductionmentioning
confidence: 99%
“…X‐ray crystallography and NMR studies have shown that peptides with the Paxillin, Leupaxin, and other LD motifs adopt a helical fold in the complexes 7‐9,15,17,20‐23,25,57,59 . Due to the placement of hydrophobic residues (mainly leucines) at 3‐residue intervals (positions 0, +3, +4, +7) along the peptide sequence, and polar or charged residues at other positions, these helices are amphipathic.…”
Section: Methodsmentioning
confidence: 99%
“…The mechanisms of Paxillin and Leupaxin binding to FAT domains display differences: PYK2‐FAT:Leupaxin and FAK‐FAT:Paxillin complexes are stable, whereas the PYK2‐FAT:Paxillin complex is more dynamic, possibly due to differences in the binding affinities of the Paxillin and Leupaxin LD motifs for the FAK and PYK2 binding sites 8 . Also, the experimental comparison of the relative strength of LD complexes and the classification of LD motifs into binders and non‐binders is challenging 17 : The measured affinities are in the order of μ M, but can display significant variations, depending on the experimental method and conditions and the peptide length 8,9,15,17,20,22,23,25,55‐60 . The up‐to‐date experimental binding affinities are collected in Supplementary Table S11.…”
Section: Introductionmentioning
confidence: 99%
“…The FAT domain is sufficient to localize to focal adhesions, through interactions mainly with paxillin, but also with cofactors or alternative ligands, such as talin or Rgnef/p190RhoGef [50][51][52]. Alternative interactions can also localize FAT to other structures, such as the T-cell receptor complex [1,38,53], or the growth cone of developing axons [54]. FRNK and PRNK maintain these functions, although without any regulatory influence from the other FAK/PYK2 regions.…”
Section: Frnk and Prnkmentioning
confidence: 99%
“…Focal Adhesion Kinase (FAK) is a multi-domain non-receptor protein tyrosine kinase (PTK) found in metazoan, but also the unicellular eukaryote Capsaspora owczarzaki [1,2]. FAK is a multifunctional protein that integrates and transduces signals perceived through integrin or growth factor receptors into adapted cytoplasmic and nuclear responses.…”
Section: Introductionmentioning
confidence: 99%